The effect of loading direction and Sn alloying on the deformation modes of Zr: An in-situ neutron diffraction study - Leo Prakash (Materials Science and Engineering: A, 2016)
Deformation modes (slip and twining) in a strongly textured model hcp alloy system (Zr–Sn) have been investigated using in-situ neutron diffraction and deformation along with complementary electron microscopy. Analysis of the evolution of the intergranular strain evolutions and intensity of specific reflections from neutron diffraction show differential influence of Sn on the extent of twinning too, depending on the deformation direction. While Sn displayed very noticeable influence on twin activity when samples were compressed along a direction that predominantly activates prismatic slip, this effect was not seen when samples were compressed along other different directions. These experimental observations were successfully simulated using a CPFE (crystal plasticity finite element) model that incorporates composition sensitive CRSS (critical resolved shear stress) for slip and composition insensitive CRSS activation of twinning. The success of the CPFE model in capturing the experimental observations with respect to twin evolution suggests that the twinning in Zr is chiefly governed by the initial crystallographic texture and the associated intergranular stress state generated during plastic deformation.